Labour Market Transitions, Shocks and Institutions in Turbulent Times: A Cross-Country Analysis - Ronald Bachmann; Rahel Felder (Institute of Labor Economics (IZA), 2018)
This paper analyses the impact of the business cycle on labour market dynamics in EU member states and the US during the first decade of the 21st century. Using unique measures of labour market flows constructed from worker-level micro data, we examine to what extent macro shocks were transmitted to national labour markets. We apply the approach by Blanchard and Wolfers (2000) to analyse the role of the interaction of macroeconomic shocks and labour market institutions for worker transitions in order to explain cross-country differences in labour market reactions in a period including the Great Recession. Our results suggest a significant influence of trade unions in channelling macroeconomic shocks. Specifically, union density moderates these impacts over the business cycle, i.e. countries with stronger trade unions experience weaker reactions of the unemployment rate and of worker transitions.
Keywords: J6; E24; E32; 330; worker flows; labour market dynamics; institutions; Great Recession